1994
DOI: 10.1111/j.1464-410x.1994.tb07558.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of urethral stricture recurrence using clean intermittent self‐catheterization

Abstract: Weekly CIC is a simple method of reducing the frequency of urethral stricture recurrence after internal urethrotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 7 publications
1
29
1
1
Order By: Relevance
“…In a study on 30 SCI patients Waller et al 12 found that patients who use hydrophilic catheters do as well or better than patients using Patients' satisfaction with the use of a hydrophilic catheter has been studied by Diokno et al 13 Of eight experienced patients who had performed CIC for a variable period 81% had a more favourable general opinion of the disposable than of the previous catheter, 81% found the disposable catheter to be more convenient and 88% thought it was easier to handle. That CIC can help in the prevention of urethral stricture recurrence has been demonstrated by Kjaergaard et al 14 Our results show that the use of Urocath-Gel 1 catheters can be a good solution for patients with a problematic use of ordinary catheters for CIC. The Urocath-Gel 1 catheters are safe and well tolerated by the majority.…”
Section: Discussionsupporting
confidence: 75%
“…In a study on 30 SCI patients Waller et al 12 found that patients who use hydrophilic catheters do as well or better than patients using Patients' satisfaction with the use of a hydrophilic catheter has been studied by Diokno et al 13 Of eight experienced patients who had performed CIC for a variable period 81% had a more favourable general opinion of the disposable than of the previous catheter, 81% found the disposable catheter to be more convenient and 88% thought it was easier to handle. That CIC can help in the prevention of urethral stricture recurrence has been demonstrated by Kjaergaard et al 14 Our results show that the use of Urocath-Gel 1 catheters can be a good solution for patients with a problematic use of ordinary catheters for CIC. The Urocath-Gel 1 catheters are safe and well tolerated by the majority.…”
Section: Discussionsupporting
confidence: 75%
“…18 Moreover, histological analysis in an animal study by Hong et al revealed that the group treated with HA/CMC exhibited Bodker et al 22 Self-catheterization 28 -12 78.0 Roosen 23 Self-catheterization 19 -6 0 Kjaergaaed et al 24 Self-catheterization 21 -12 19.1 Mkony 25 Hydraulic urethral dilatation 23 <0.5 6 8.7…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, video documentation and stent placing are impossible when using dilators. Regardless of the protocol details, the practice of CIC after initial urethral dilation, whether carried out by the patient himself or other family members, is known to keep the urethra wide for the longest possible time; thus, avoiding restricture formation [6, 7, 8]. …”
Section: Discussionmentioning
confidence: 99%